Sexual and reproductive health for young adults in Colombia: Teleconsultation using mobile devices (2014)
Background: Sexual risk behaviors associated with poor information on sexuality have contributed to major public health problems in the area of sexual and reproductive health in teenagers and young adults in Colombia. Objective: To report our experience with the use of DoctorChat Mobile to provide sexual education and information among university students in Bogota, Colombia, and knowledge about the sexual risk factors detected among them. Methods: A mobile app that allows patients to ask about sexual and reproductive health issues was developed. Sexual and reproductive risk behaviors in a sample of young adults were measured before and after the use of the app through the validated survey Family Health International (FHI) Behavioral Surveillance Survey (BSS) for Use With Adults Between 15 and 49 Years. A nonprobabilistic convenience recruitment was undertaken through the study's webpage. After completing the first survey, participants were allowed to download and use the app for a 6-month period (intervention), followed by completion of the same survey once again. For the inferential analysis, data was divided into 3 groups (dichotomous data, discrete quantitative data, and ordinal data) to compare the results of the questions between the first and the second survey. The study was carried out with a sample of university students between 18 and 29 years with access to mobile phones. Participation in the study was voluntary and anonymous. Results: A total of 257 subjects met the selection criteria. The preintervention survey was answered by 232 subjects, and 127 of them fully answered the postintervention survey. In total, 54.3% (69/127) of the subjects completed the survey but did not use the app, leaving an effective population of 58 subjects for analysis. Of these subjects, 53% (31/58) were women and 47% (27/58) were men. The mean age was 21 years, ranging between 18 and 29 years. The differences between the answers from both surveys were not statistically significant. The main sexual risk behaviors identified in the population were homosexual intercourse, nonuse of condoms, sexual intercourse with nonregular and commercial partners, the use of psychoactive substances, and lack of knowledge on symptoms of sexually transmitted diseases and HIV transmission. Conclusions: Although there were no differences between the pre-and postintervention results, the study revealed different risk behaviors among the participating subjects. These findings highlight the importance of promoting high-impact educational strategies on this matter and the importance of providing teenagers and young adults with easily accessible tools with reliable health information, regardless of their socioeconomic status.